Manual of neonatal respiratory care - Sinha, Sunil K.; Donn, Steven M. (Springer US, 2012)
This popular book covers the "how-to" of the respiratory care of newborns in outline format.  It includes case studies for self-review and is illustrated with high quality radiographic images, figures, tables, and algorithms.  Written and edited by international experts, the Third Edition is a thorough update and remains a convenient source of practical information on respiratory physiology, exam techniques, tips for performing procedures, radiography, ventilation, pain management, transport, and discharge planning. ·Up-to-date clinical information from world experts ·Case studies ·Easy-to-consult outline format ·Condensed information about all of the major mechanical ventilators (e.g., modes, displays, and alarms) "The extent of coverage, easy readability, superb organization [and] ...practical pearls make [this book] worthwhile...simply a great bargain."  --Journal of Perinatology (review of a previous edition)